Advances in the high bootstrap fraction regime on DIII-D towards the Q = 5 mission of ITER steady state. (20th March 2017) - Qian, J.P.; Garofalo, A.M.; Gong, X.Z.; Ren, Q.L.; Ding, S.Y.; Solomon, W.M.; Xu, G.S.; Grierson, B.A.; Guo, W.F.; Holcomb, C.T.; McClenaghan, J.; McKee, G.R.; et al.
Abstract: Recent EAST/DIII-D joint experiments on the high poloidal beta β P regime in DIII-D have extended operation with internal transport barriers (ITBs) and excellent energy confinement ( H 98 y 2 1.6) to higher plasma current, for lower q 95 ⩽ 7.0, and more balanced neutral beam injection (NBI) (torque injection < 2 Nm), for lower plasma rotation than previous results (Garofalo et al, IAEA 2014, Gong et al 2014 IAEA Int. Conf. on Fusion Energy ). Transport analysis and experimental measurements at low toroidal rotation suggest that the E × B shear effect is not key to the ITB formation in these high β P discharges. Experiments and TGLF modeling show that the Shafranov shift has a key stabilizing effect on turbulence. Extrapolation of the DIII-D results using a 0D model shows that with the improved confinement, the high bootstrap fraction regime could achieve fusion gain Q = 5 in ITER at β N 2.9 and q 95 7. With the optimization of q (0), the required improved confinement is achievable when using 1.5D TGLF-SAT1 for transport simulations. Results reported in this paper suggest that the DIII-D high β P scenario could be a candidate for ITER steady state operation.